Welcome to Westonci.ca, where you can find answers to all your questions from a community of experienced professionals. Get detailed and accurate answers to your questions from a community of experts on our comprehensive Q&A platform. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
To solve the equation [tex]\((x-3)^2 + 2(x-3) - 8 = 0\)[/tex], we can use substitution to make the process simpler.
Let's define a new variable [tex]\( u \)[/tex] such that:
[tex]\[ u = x - 3 \][/tex]
Now, substitute [tex]\( u \)[/tex] back into the equation:
[tex]\[ (u)^2 + 2(u) - 8 = 0 \][/tex]
We now have a quadratic equation in terms of [tex]\( u \)[/tex]:
[tex]\[ u^2 + 2u - 8 = 0 \][/tex]
To solve this quadratic equation, we can use the quadratic formula:
[tex]\[ u = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
For our equation [tex]\( u^2 + 2u - 8 = 0 \)[/tex], the coefficients are:
[tex]\[ a = 1, \quad b = 2, \quad c = -8 \][/tex]
First, calculate the discriminant [tex]\( \Delta \)[/tex]:
[tex]\[ \Delta = b^2 - 4ac = 2^2 - 4 \cdot 1 \cdot (-8) = 4 + 32 = 36 \][/tex]
Since the discriminant is positive, we have two distinct real solutions. Now, solve for [tex]\( u \)[/tex]:
[tex]\[ u = \frac{-b \pm \sqrt{\Delta}}{2a} = \frac{-2 \pm \sqrt{36}}{2 \cdot 1} = \frac{-2 \pm 6}{2} \][/tex]
This gives us two potential values for [tex]\( u \)[/tex]:
[tex]\[ u_1 = \frac{-2 + 6}{2} = \frac{4}{2} = 2 \][/tex]
[tex]\[ u_2 = \frac{-2 - 6}{2} = \frac{-8}{2} = -4 \][/tex]
Recalling our substitution [tex]\( u = x - 3 \)[/tex], we substitute back to find [tex]\( x \)[/tex]:
[tex]\[ 2 = x - 3 \implies x = 2 + 3 = 5 \][/tex]
[tex]\[ -4 = x - 3 \implies x = -4 + 3 = -1 \][/tex]
Therefore, the solutions to the equation [tex]\((x-3)^2 + 2(x-3) - 8 = 0\)[/tex] are:
[tex]\[ x = 5 \quad \text{and} \quad x = -1 \][/tex]
Given the options, the correct answer is:
[tex]\[ \boxed{x = -1 \text{ and } x = 5} \][/tex]
Let's define a new variable [tex]\( u \)[/tex] such that:
[tex]\[ u = x - 3 \][/tex]
Now, substitute [tex]\( u \)[/tex] back into the equation:
[tex]\[ (u)^2 + 2(u) - 8 = 0 \][/tex]
We now have a quadratic equation in terms of [tex]\( u \)[/tex]:
[tex]\[ u^2 + 2u - 8 = 0 \][/tex]
To solve this quadratic equation, we can use the quadratic formula:
[tex]\[ u = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
For our equation [tex]\( u^2 + 2u - 8 = 0 \)[/tex], the coefficients are:
[tex]\[ a = 1, \quad b = 2, \quad c = -8 \][/tex]
First, calculate the discriminant [tex]\( \Delta \)[/tex]:
[tex]\[ \Delta = b^2 - 4ac = 2^2 - 4 \cdot 1 \cdot (-8) = 4 + 32 = 36 \][/tex]
Since the discriminant is positive, we have two distinct real solutions. Now, solve for [tex]\( u \)[/tex]:
[tex]\[ u = \frac{-b \pm \sqrt{\Delta}}{2a} = \frac{-2 \pm \sqrt{36}}{2 \cdot 1} = \frac{-2 \pm 6}{2} \][/tex]
This gives us two potential values for [tex]\( u \)[/tex]:
[tex]\[ u_1 = \frac{-2 + 6}{2} = \frac{4}{2} = 2 \][/tex]
[tex]\[ u_2 = \frac{-2 - 6}{2} = \frac{-8}{2} = -4 \][/tex]
Recalling our substitution [tex]\( u = x - 3 \)[/tex], we substitute back to find [tex]\( x \)[/tex]:
[tex]\[ 2 = x - 3 \implies x = 2 + 3 = 5 \][/tex]
[tex]\[ -4 = x - 3 \implies x = -4 + 3 = -1 \][/tex]
Therefore, the solutions to the equation [tex]\((x-3)^2 + 2(x-3) - 8 = 0\)[/tex] are:
[tex]\[ x = 5 \quad \text{and} \quad x = -1 \][/tex]
Given the options, the correct answer is:
[tex]\[ \boxed{x = -1 \text{ and } x = 5} \][/tex]
Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.